Interferensi Sintaksis Bahasa Dani dalam Bahasa Indonesia oleh Penutur Dani - Arina Kharisatul Kamilah; Vina Vitri Alawiyah; Redika Cindra Reranta (Jurnal Bahastra, 2026)
This study examines syntactic interference in the Indonesian language as used by speakers of the Dani ethnic group in Papua, a phenomenon arising from the interaction between regional language systems and standard Indonesian. The research addresses how differences in syntactic structures manifest when Dani speakers employ Indonesian in everyday communication. Using a qualitative descriptive approach, data were collected through documentary observation, literature review, and note-taking techniques, as well as attentive listening to language use across various media, including digital video platforms. The findings reveal several forms of syntactic interference, including deviations in sentence structure patterns, the addition of sentence elements, and the incorporation of local phatic expressions within Indonesian utterances. These patterns indicate that the Dani language exerts a significant influence on the syntactic realization of Indonesian among its speakers. The study argues that such interference reflects not only linguistic transfer but also the persistence of cultural and communicative norms embedded in local languages. These findings contribute to the field of sociolinguistics and syntax, particularly in understanding bilingual language behavior and its implications for language learning and policy.